2016
DOI: 10.1007/s10853-016-0547-7
|View full text |Cite
|
Sign up to set email alerts
|

Creating three-dimensional (3D) fiber networks with out-of-plane auxetic behavior over large deformations

Abstract: Fiber networks with out-of-plane auxetic behavior have been sporadically investigated. One of the major challenges is to design such materials with giant negative Poissons ratio over large deformations. Here in, we report a systematic investigation to create three-dimensional (3D) fiber networks in the form of needle punched nonwoven materials with out-of-plane auxetic behavior over large deformations via theoretical modeling and extensive set of experiments. The experimental matrix has encapsulated the key pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…ref. 30 ). The large discrepancy between the tensile forces needed to extend a slender fibre and the compressive forces required to make it buckle suggests that a smaller fraction of fibres inclined towards the loading direction would be sufficient to cause the out-of-plane deflection of transversally oriented fibre segments.…”
Section: Resultsmentioning
confidence: 99%
“…ref. 30 ). The large discrepancy between the tensile forces needed to extend a slender fibre and the compressive forces required to make it buckle suggests that a smaller fraction of fibres inclined towards the loading direction would be sufficient to cause the out-of-plane deflection of transversally oriented fibre segments.…”
Section: Resultsmentioning
confidence: 99%
“…Such structures induced in-plane auxetic behavior of the nonwoven fabrics. Bhullar et al [ 24 , 25 ] also used the rotating square geometry in polycaprolactone nanofiber webs (membranes) made by the electrospinning procedure and laser cutting. Rawal et al [ 24 ] developed 3D polyester needle-punched webs with out-of-plane auxetic behavior by adjusting the needle boards‘ direction in a needle-punching process (and, consequently, the proportion of fibers in the through-thickness direction of the webs).…”
Section: Introductionmentioning
confidence: 99%
“…Bhullar et al [ 24 , 25 ] also used the rotating square geometry in polycaprolactone nanofiber webs (membranes) made by the electrospinning procedure and laser cutting. Rawal et al [ 24 ] developed 3D polyester needle-punched webs with out-of-plane auxetic behavior by adjusting the needle boards‘ direction in a needle-punching process (and, consequently, the proportion of fibers in the through-thickness direction of the webs). Rawal et al [ 25 ] analyzed needle-punched nonwoven fabrics with out-of-plane auxetic behavior by deconstructing the anisotropic structure, and presented analytical models of the modulus and an in-plane Poisson’s ratio.…”
Section: Introductionmentioning
confidence: 99%
“…While our work has shown that heated compression can enhance the auxetic effect in nonwovens, Rawal et al have also examined the effect of process parameters during the needle punching operation for nonwovens and found that increasing the punch density (decreasing the spacing between fiber columns) can increase the auxetic effect in these fabrics. 46,47 Extending the auxetic behavior of needlepunched nonwovens, work by Dubrovski et al have produced in-plane auxeticity in needle-punched nonwovens by using laser cutting to produce a rotating square pattern in the fabric. 48 This paper builds on what is known about auxetic nonwovens by examining the auxetic character of a stiff felt nonwoven.…”
Section: Introductionmentioning
confidence: 99%